Faktor yang Berhubungan dengan Kepatuhan Konsumsi Tablet Tambah Darah pada Remaja Putri: Systematic Literature Review - Kartipani Handina; Musafaah Musafaah; Fujiati Fujiati; Meitria Syahadatina Noor; Ermina Istiqomah (Malahayati Nursing Journal, 2026)
ABSTRACT Anemia among adolescent girls remains an important public health problem because it affects learning capacity, physical fitness, and reproductive health in later life. Iron Supplementation Tablets (Tablet Tambah Darah/TTD) programs have been widely implemented; however, the success of these programs is highly dependent on adherence to tablet consumption. This study aimed to synthesize scientific evidence regarding factors associated with adherence to iron supplementation tablet consumption among adolescent girls. This study was conducted as a systematic literature review using the PRISMA 2020 guidelines and the PECO framework. Literature searching was carried out through Google Scholar, ScienceDirect, and PubMed/PMC for primary research articles published in Indonesian or English between 2021 and 2026. A total of 20 articles met the inclusion criteria and were included in the qualitative synthesis. The review found that the factors most consistently associated with adherence were knowledge of anemia and iron supplementation tablets, understanding of tablet-taking instructions, information exposure, family support, peer support, teacher and health worker support, attitudes and motivation, tablet availability, and the quality of school-based program implementation. The most frequently reported barriers were forgetfulness, unpleasant taste, nausea or side effects, the perception of not needing the tablets, and inadequate reminders or counseling. Intervention studies also showed that digital reminders, app-based education, and strengthened school programs could improve adherence. Improving adherence to iron supplementation tablet consumption among adolescent girls requires a multilevel approach that integrates education, clear instruction communication, social support, tablet availability, and sustainable reminder strategies. Keywords: Iron Supplementation, Adherence, Adolescent Girls, Anemia. ABSTRAK Anemia pada remaja putri masih menjadi masalah kesehatan masyarakat yang penting karena berdampak pada kapasitas belajar, kebugaran, dan kesehatan reproduksi pada masa mendatang. Program suplementasi Tablet Tambah Darah (TTD) telah diterapkan secara luas, namun keberhasilan program sangat ditentukan oleh kepatuhan konsumsi. Penelitian ini bertujuan menyintesis bukti ilmiah mengenai faktor-faktor yang berhubungan dengan kepatuhan konsumsi TTD pada remaja putri. Penelitian disusun secara systematic literature review dengan acuan PRISMA 2020 dan kerangka PECO. Penelusuran dilakukan pada Google Scholar, Sciencedirect, dan PubMed/PMC terhadap artikel primer berbahasa Indonesia atau Inggris tahun 2021–2026. Sebanyak 20 artikel diinklusi dalam sintesis kualitatif. Hasil review menunjukkan bahwa faktor yang paling konsisten berhubungan dengan kepatuhan adalah pengetahuan tentang anemia dan TTD, pemahaman instruksi minum tablet, paparan informasi, dukungan keluarga, dukungan teman sebaya, dukungan guru/tenaga kesehatan, sikap dan motivasi, ketersediaan tablet, serta kualitas implementasi program sekolah. Hambatan yang paling sering muncul adalah lupa, rasa tidak enak, mual/efek samping, persepsi tidak membutuhkan tablet, dan lemahnya pengingat atau konseling. Studi intervensi menunjukkan bahwa pengingat digital, edukasi berbasis aplikasi, dan penguatan program sekolah dapat meningkatkan kepatuhan. peningkatan kepatuhan konsumsi TTD pada remaja putri memerlukan pendekatan multilevel yang menggabungkan edukasi, komunikasi instruksi yang jelas, dukungan sosial, ketersediaan tablet, dan strategi pengingat yang berkelanjutan. Kata Kunci: Tablet Tambah Darah, Kepatuhan, Remaja Putri, Anemia.